Ni nanoparticles on RGO as reusable heterogeneous catalyst: effect of Ni particle size and intermediate composite structures in C–S cross-coupling reaction - Sengupta, Debasish; Bhowmik, Koushik; De, Goutam; Basu, Basudeb (Beilstein Journal of Organic Chemistry, 2017)
The present work demonstrates the C–S cross-coupling reaction between aryl halides and thiols using nickel nanoparticles (Ni NPs) supported on reduced graphene oxide (Ni/RGO) as a heterogeneous catalyst. It is observed that the uniformly dispersed Ni NPs supported on RGO could exhibit excellent catalytic activity in C–S cross-coupling reactions and the catalytic application is generalized with diverse coupling partners. Although the electron-rich planar RGO surface helps in stabilizing the agglomeration-free Ni NPs, the catalytic process is found to occur involving Ni(II) species and the recovered catalyst containing both Ni(0)/Ni(II) species is equally efficient in recycle runs. A correlation of loading of Ni species, size of NPs and the intermediate Ni-related heterostructures formed during the catalytic process has been established for the first time, and found to be best in the C–S cross-coupling reaction for Ni(0) and Ni(II) NPs of the average sizes 11–12 nm and 4 nm, respectively.
Keywords: C–S cross-coupling; heterogeneous catalyst; Ni nanoparticle; reduced graphene oxide; thioether